Enumeration Class of Polyominoes Defined by Two Column - Mohommed, Eman F.; Ibrahim, Haslinda; Ahmad, Nazihah (IOSR Journals, 2017)
Abacus diagram is a graphical representation for any partition μ of a positive integer t. This study presents the bead positions as a unite square in the graph and de ne a special type of e-abacus called nested chain abacus which is represented by the connected partition. Furthermore, we redefined the polyominoes as a special type of e-abacus diagram. Also, this study reveals new method of enumerating polyominoes special design when e=2